Mississippi Medical Reserve Corps: Moving Mississippi From Emergency Planning to Response Ready. Issue 1 (January 2017) - McCormick, Lisa C.; Fifolt, Matthew; Mercer, Caroline; Pevear, Jesse; Wilson, Jonathan
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: The purpose of this study was to identify factors that might impact a Medical Reserve Corps (MRC) volunteer's decision to respond to an emergency event. The 2 primary goals of this survey were to (1) establish realistic planning assumptions regarding the use of volunteers in health care emergency responses, and (2) determine whether barriers to volunteer participation could be addressed by MRC units to improve volunteer response rates. Design: An anonymous online survey instrument was made available via Qualtrics through a customized URL. For the purpose of distribution, the Mississippi State Department of Health sent an electronic message that included the survey link to all MRC volunteers who were registered with the Mississippi Responder Management System (MRMS) as of September 2014. Results: Approximately 15% of those surveyed indicated they would be available and able to deploy within 24 hours. The most common factors reported in terms of respondent decisions to deploy included risk to personal health (61.2%), length of deployment (58.8%), and the security of the deployment area (55.3%). In addition, 67% of respondents indicated that extended periods of deployment would have a negative financial impact on their lives. Respondents who have had training or previous deployment experience reported having greater knowledge of potential response roles, increased comfort in their ability to respond with the MRC, and increased confidence in responding to differing public health emergencies. Conclusions: Barriers to MRC volunteers being able to deploy should be addressed by each MRC unit. Issues such as risk to personal safety while on deployment, site security, and length of deployment should be considered by planners and those solutions communicated to MRC members during trainings. Emergency plans utilizing MRC volunteers will require significant evaluation to assess the risk of relying on an expected resource that could be severely limited during an actual emergency.